Peran Guru Wali Kelas Mengatasi Terjadinya Self Harm Pada Siswa Kelas VII MTs. Raudhatul Hasaniyah - Kisma Aruna Jalanidi; Nurul Saila; Ani Sulianti (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The role of the MTs class teacher. Raudhatul Hasaniyah is really needed in overcoming the occurrence of self-harm in class VII. It is hoped that class teachers will be able to overcome and prevent self-harm. In general, the acts of self-harm carried out by several students in class VII have their own reasons. One of them is a lack of emotional control in students so that they do self-harm, or there is also some internal or external pressure. This is where the researcher wants and is interested in uncovering the problem of the role of class teachers in overcoming the occurrence of self-harm in class VII MTs. Raudhatul Hasaniyah.The method used by researchers is a qualitative approach with qualitative descriptive data research type, the research location chosen is MTs. Raudhatul Hasaniyah Probolinggo City. The data sources used are primary and secondary data, with research data collection techniques including: observation, interviews and documentation. Data analysis techniques use data reduction, data presentation and conclusions. Meanwhile, to check the validity of the data using triangulation techniques.The research results show that the role of class teachers in overcoming self-harm is good. The actions taken are appropriate, providing motivation which is very important to help control unstable emotions in teenagers, carrying out evaluations and providing regular guidance so that students are more open to problems is the right action.